(untitled) (The Journal of Academic Development, 2025)
Impulse buying is a spontaneous and unplanned purchasing behavior influenced by psychological, social, and environmental factors. With the rapid expansion of e-commerce, particularly in Nepal, online marketing strategies, social media influence, and reference groups have emerged as essential drivers of impulsive buying, especially in online apparel shopping. This study examines the influence of reference groups on impulsive buying behavior and inquires into the mediating role of hedonic shopping behavior within the framework of the Stimulus-Organism-Response (S-O-R) model. Using a descriptive and causal-comparative research design, data were collected from 400 respondents in Butwal Sub-Metropolitan City through a structured questionnaire. The research findings indicate that reference groups significantly influence impulsive buying, both directly and indirectly, through hedonic shopping behavior of the consumer. However, the mediating effect of hedonic shopping behavior is relatively weak, suggesting that reference groups have a more direct impact on impulsive purchasing decisions than the pleasure derived from shopping. The study contributes to consumer behavior literature by highlighting the role of reference groups in online retail environments and providing insights for online marketers to develop targeted strategies that leverage social evidence and hedonic appeal to improve sales. Additionally, this research has implications for policymakers in ensuring ethical online marketing practices.